ترکیہ میں جمہوری دورحکومت کا ارتقاء ، مذہبی کاوشیں اور صدر رجب طیب اردگان: Evolving Stages of the Democratic Era in Turkeye, Religious Efforts and President Recep Tayyip Erdogan (Khairulummah, 2023)
Turkeye is a very important country in terms of location. Because Turkeye is a gateway between Asia and Europe. A hundred years ago, the system of Islamic caliphate was prevalent in Turkeye for a long time, but in 1924, due to the conspiracies of western countries, the caliphate was abolished, and a democratic government was established. Due to which secular life system started to be promoted in Turkeye instead of Islamic life system. The effects of which started coming in the form of restrictions on religious schools and institutions as well as religious. But after a long time, during the period of Adnan Menderes, the tendency towards Islamic principles and life system started to increase again, the effects of which are present before us. After the end of the caliphate in Turkeye, there is a long story from the beginning of the democratic regime to the present era, that it is very important to have such a change in an Islamic country where a Muslim becomes a victim of problems in performing his duties with ease and freedom, then after decades, moving towards the Islamic revolution again.Therefore, in this article, we will briefly discuss on the stages from the evolution stages of the democratic period of Turkeye to the current President Recep Tayyip Erdogan. Actions taken in the early days of the democratic government and their effects will also be highlighted in detail on the actions and achievements of President Tayyip Erdogan for Turkeye.